Unintended consequences of health policy programs and policies : workshop summary - Young, Wendy Babcock, 1947- (National Academy Press, 2001)
"The Robert Wood Johnson (RWJ) Health Policy Fellowships Program of the Institute of Medicine (IOM) conducted a workshop on August 22, 2000, on the subject of unintended consequences of health policy programs and policies. The purpose of the workshops was to gain a better understanding of why this phenomenon is a frequent and consequential by-product of major health policy programs."--Page 1